The Analgesic Efficacy of Paracetamol Versus Ketorolac in Day-case Gynaecological Laparoscopic Procedure: A Comparative Study - Shaheen, Md Shafiul Alam; Rahman, Md Khalilur; Sardar, Kawsar; Rahman, Md Mushfiqur; Hasan, Md Mahabubul; Chowdhury, AKM Nurnobi (Journal of the Bangladesh Society of Anaesthesiologists, 2017)
Background: Gynaecological laparoscopy is a commonly performed procedure. Providing anesthesiafor this can present a challenge, particularly in the day surgery population. Poor analgesia, nausea andvomiting can cause distress to the patient and increased cost for the health system, because of overnightadmission. In this review we discuss anesthetic and analgesic techniques for day case gynaecologicallaparoscopy. Objectives: Our study is undertaken to compare the efficacy of intravenous paracetamol versus ketorolacfor post operative analgesia after gynaecological day case laparoscopic procedures. Method: Sixty (60) female patients 20 – 40 years of age, of ASA I/II were randomized into two equalgroups of 30 patients each. Patients of group A received intravenous paracetamol 1gm and group Breceived intravenous ketorolac 30mg just after induction of general anesthesia. Postoperative pain wasevaluated by standard 10cm linear visual analogue scale (VAS) at different time intervals. When VAS wasmore than 3 rescue analgesic 50mg tramadol intravenously stat was given. Results: In group A that was paracetamol group and group B that was ketorolac group the visual analoguescale (VAS) almost similar but total analgesic consumption in ketorolac group were slightly higher thanparacetamol group. In paracetamol group 4 patients and in ketorolac group 6 patients required rescueanalgesic dose. Conclusion: Our results indicate that IV paracetamol has better analgesic potency than IV ketorolac forpostoperative analgesia after day case gynaecological laparoscopic procedure. JBSA 2017; 30(2): 90-95